-9(6+u)-2u=-2

Simple and best practice solution for -9(6+u)-2u=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(6+u)-2u=-2 equation:


Simplifying
-9(6 + u) + -2u = -2
(6 * -9 + u * -9) + -2u = -2
(-54 + -9u) + -2u = -2

Combine like terms: -9u + -2u = -11u
-54 + -11u = -2

Solving
-54 + -11u = -2

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + -11u = -2 + 54

Combine like terms: -54 + 54 = 0
0 + -11u = -2 + 54
-11u = -2 + 54

Combine like terms: -2 + 54 = 52
-11u = 52

Divide each side by '-11'.
u = -4.727272727

Simplifying
u = -4.727272727

See similar equations:

| 0.4b=0.8 | | 6z-14=4a+2 | | 3/6-5/8 | | 2/3a=5/3 | | 1/4c=5/3 | | n/.14=15 | | 5x+4y=12y | | -6y=-4+24 | | g(x)=sqrx+1 | | 4/3(6x-9)-10 | | 9.124-.3=x | | x^2+y^2-4x-2y-11=0 | | 12a^2-9a-21=0 | | x+2x=2x(6) | | y^2+y-x-4=0 | | p(x)=2x^2+8x+5 | | 5.58b=8.68+3.68b | | F(x)=log(x+3)-7 | | -6xf=8.04 | | -8*x+29=-3 | | 4(x^2-8x+16)+14=0 | | (X-4)+(11)+(2x-25)=x+28 | | 12.5*31.25= | | X*8=10 | | 6y-4=12y+26 | | -4(8+5n)=-24 | | 4.1-2x=-10.9 | | 5s-10s=20 | | y^2dx-(2x+3)dy=0 | | w-(-43)=8 | | 30x=10x+10 | | 0.6x+0.8=1 |

Equations solver categories